2015
DOI: 10.1021/acs.jchemed.5b00483
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Aggregation-Caused Quenching versus Aggregation-Induced Emission: A Visual Teaching Technology for Undergraduate Chemistry Students

Abstract: A laboratory experiment visually exploring two opposite basic principles of fluorescence of aggregation-caused quenching (ACQ) and aggregation-induced emission (AIE) is demonstrated. The students would prepared two salicylaldehyde-based Schiff bases through a simple one-pot condensation reaction of one equiv of 1,2-diamine with 2 equiv of salicylaldehyde. The resulting fluorescent dyes have similar chemical structures but possess ACQ and AIE properties, respectively. Their ACQ/AIE properties and pH sensing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
175
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(185 citation statements)
references
References 23 publications
1
175
1
Order By: Relevance
“…Fluorescence quenching in the solid and aggregated states or at high concentration of the fluorophores, also known as aggregation caused quenching (ACQ), is a common phenomenon for organic luminescent materials . The ACQ effect is more harmful and challenging during practical applications in organic light emitting diodes (OLEDs), light‐emitting electrochemical cell applications and development of optoelectronic devices . However, fluorophores with solid state/aggregated emission have more advantages in above mentioned applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence quenching in the solid and aggregated states or at high concentration of the fluorophores, also known as aggregation caused quenching (ACQ), is a common phenomenon for organic luminescent materials . The ACQ effect is more harmful and challenging during practical applications in organic light emitting diodes (OLEDs), light‐emitting electrochemical cell applications and development of optoelectronic devices . However, fluorophores with solid state/aggregated emission have more advantages in above mentioned applications .…”
Section: Introductionmentioning
confidence: 99%
“…The ACQ effect is more harmful and challenging during practical applications in organic light emitting diodes (OLEDs), light‐emitting electrochemical cell applications and development of optoelectronic devices . However, fluorophores with solid state/aggregated emission have more advantages in above mentioned applications . Although a plenty of research articles and excellent organic fluorophores have been reported, most of the reported systems are highly emissive in the solution and weakly or non‐emissive in the solid state .…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the aggregation effects on III in THF (good solvent) and deionized water (poor solvent) at different ratios (Figure S8, Supporting Information). The fluorescence intensity decreases as the water content increases, which is consistent with the aggregation‐caused quenching (ACQ) effect of the fluorescence …”
Section: Resultsmentioning
confidence: 99%
“…Adding water to the THF solution of a molecule will cause the aggregates and result in an enhancement of the emission. This typical process is called the AIE effect …”
Section: Resultsmentioning
confidence: 99%